Four-family =1 supersymmetric Pati–Salam models from intersecting D6-branes. (1st June 2022) - Li, Tianjun; Sun, Rui; Zhang, Chi
Abstract: We investigate the construction of four-family  = 1 supersymmetric Pati–Salam models from Type IIA T 6 / Z 2 × Z 2 orientifold with intersecting D 6-branes. Utilizing the deterministic algorithm introduced in He W, Li T and Sun R (2021 arXiv: hep-th/2112.09632 ), we obtain 274 types of models with three rectangular tori and distinct gauge coupling relations at string scale, while 6 types of models with two rectangular tori and one tilted torus. In both cases, there exists a class of models with gauge coupling unification at string scale. In particular, for the models with two rectangular tori, one tilted torus and gauge coupling unification, the gaugino condensations are allowed, and thus supersymmetry breaking and moduli stabilization are possible for further phenomenological study.